Response surface analysis of lipase production by freely suspended Rhizopus arrhizus - Elibol, M; Ozer, D (Elsevier Sci Ltd, 2002)
The combined effects of initial glucose concentration and inducer (corn oil) concentration on lipase production by freely suspended Rhizopus arrhizus were investigated using response surface methodology (RSM). A 2(2) full-factorial central composite design was employed for experimental design and analysis of the results. The optimum glucose and inducer concentrations were found to be 1.1 and 3.3 g/l, respectively. In these conditions, the biomass concentration of 2.4 g/l with a lipolytic activity of 370 mumol/l min was attained. These results are in close agreement with the model parameters. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: lipase; Rhizopus arrhizus; response surface methodology; glucose; inducer (corn oil)